Pengembangan Sistem Travel Order Perjalanan Dinas Berbasis Android (Studi Kasus Kantor Pusat BPJS Ketenagakerjaan) - Anggit Chalilur Rahman; Faizatul Amalia; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Submission of official travel BPJS Ketenagakerjaan Headquarters is a submission process carried out by employees to the head of the division. At this time, the BPJS Ketenagakerjaan Headquarters uses a website-based information system in the process of submitting official travel. However, there is the problem of the system which can only be accessed through a local server, so it is not possible to submit and approve official travel trips outside the office, and the systems that have not been directly integrated with the data in determining the accommodation to be used. Therefore, this research developed an android-based official travel application system that uses Application Programming Interface (API) technology to facilitate employees in determining the airline to be used. Also, the selection of an Android-based platform can also improve the functionality of the daily system because it is connected directly to the gadgets of employees. This development uses the waterfall development model, because the list of needs has been determined from the beginning. From this research, a travel information system for travel orders with 27 functional and one non-functional requirement was usability needs was produced. The system is intended for three types of actors namely order officers, Approval officials, and admins. This system has been tested by unit testing, validation testing, and usability testing using the System Usability Scale (SUS) questionnaire. Unit tests produce 100% valid status in six test cases and validation tests produce 100% valid status in 55 test cases, while usability testing results in an average SUS score of 68.75 on the order side, as well as an average SUS score with the number 75 on the official approval and admin.